Resistance of the Indonesian Ahmadiyah Congregation in 2013: Case study of Batu Putih Village, Pelawan District - Sukarddin, Sukarddin; Suhadak, Totok (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2024)
This study discusses the organizational resistance of the Indonesian Ahmadiyya Congregation. The purpose of this writing is to analyze the resistance of the Indonesian Ahmadiyya Congregation in responding to the 2013 conflict: Case study of Batu Putih Village, Pelawan District. The research methods used include historical research, namely heuristics, criticism, interpretation, and historiography. Data collection techniques in this study used interview, observation, and documentation techniques with data reduction, data presentation, and verification. The results of the research show that the resistance of the Indonesian Ahmadiyya Congregation leads to positive social humanitarian activities. After this action, the congregation becomes more active in religious activities. traditional medicine (homeopathy), cornea donors, and cooperation between religious organizations and government agencies. So, the mass action that took place in November 2013 did not discourage members of the Ahmadiyya Congregation from abandoning their beliefs. On the contrary, this action made JAI more solid